2021
DOI: 10.1021/acs.inorgchem.1c01513
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent Quaternary Ag(InxGa1–x)S2/GaSy Core/Shell Quantum Dots Prepared Using Dithiocarbamate Compounds and Photoluminescence Recovery via Post Treatment

Abstract: Cadmium-free quantum dots (QDs) consisting of silver–indium–gallium–sulfide (AIGS) quaternary semiconductors were successfully synthesized using a metal–dithiocarbamate complex with sufficiently high reactivity to produce metal sulfides. The introduction of a gallium diethyldithiocarbamate precursor decreased the reaction temperature to produce active intermediates, which were subsequently converted into AIGS QDs at 150 °C with silver and indium acetates. Because of the low reaction temperature, AIGS QDs with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
68
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 38 publications
(69 reference statements)
2
68
2
Order By: Relevance
“… 22 While uniformly incorporating less-reactive gallium was a substantial challenge, we found that gallium tris( N , N ′-diethyldithiocarbamate) (Ga[DDTC] 3 ) works well owing to its high reactivity in the production of metal sulfides, resulting in the successful synthesis of AIGS QDs at lower temperature; this process involved nearby ions (Ag + and In 3+ ) that were mixed in the reaction solution in the form of acetates. 23 AIGS QDs with different In/Ga ratios were obtained with a well-controlled composition and crystal structure by changing the amount of Ga(DDTC) 3 , which acts as the source of both gallium and sulfur. However, the PL QY of the AIGS QDs decreased significantly upon increasing the amount of Ga(DDTC) 3 , which is due to the electron-accepting nature of the decomposition products of the DDTC ligands that are presumably bound on the surface.…”
Section: Introductionmentioning
confidence: 99%
“… 22 While uniformly incorporating less-reactive gallium was a substantial challenge, we found that gallium tris( N , N ′-diethyldithiocarbamate) (Ga[DDTC] 3 ) works well owing to its high reactivity in the production of metal sulfides, resulting in the successful synthesis of AIGS QDs at lower temperature; this process involved nearby ions (Ag + and In 3+ ) that were mixed in the reaction solution in the form of acetates. 23 AIGS QDs with different In/Ga ratios were obtained with a well-controlled composition and crystal structure by changing the amount of Ga(DDTC) 3 , which acts as the source of both gallium and sulfur. However, the PL QY of the AIGS QDs decreased significantly upon increasing the amount of Ga(DDTC) 3 , which is due to the electron-accepting nature of the decomposition products of the DDTC ligands that are presumably bound on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…[17] Additionally, it was reported that the metal-dithiocarbamate complex had sufficiently high reactivity to produce metal sulfides. [9,[22][23][24][25][26] Based on the above considerations, here, the luminescent AgInS 2 @In 2 S 3 core@shell nanoparticles were fabricated via the reaction of preformed Ag…”
Section: Introductionmentioning
confidence: 99%
“…[3] Among IB-IIIA-VIA 2 materials, the AgInS 2 nanostructures with direct band gap exhibited strong photoluminescence (PL) in the visible-light wavelength region and had attracted extensive attention in recent research. [5][6][7][8][9] Moreover, it was found that the PL properties of AgInS 2 nanostructures were strongly influenced by the defects, such as the non-irradiative recombination of excited carriers trapped by surface defects (e.g., the dangling bonds on the nanomaterial surface), or the donor-acceptor levels and/or surface traps resulted in the defect emission, [10,11] which was characterized by the large stokes shift and broad emission spectrum. For the application of AgInS 2 nanostructures, how to eliminate defect emission and enhance band edge emission was a very important topic.…”
mentioning
confidence: 99%
See 2 more Smart Citations